Impact of Green Human Resource Management on Service Recovery: Mediating Role of Environmental Commitment and Moderation of Transformational Leadership - Iftikhar, Umer; Zaman, Khansa; Rehmani, Mahmood; Ghias, Wajeeha; Islam, Tahir (Frontiers in Psychology, 2021)
Greening of the hotel industry can be achieved through employees' green service recovery performance to determine environment-friendly or unfriendly issues driven by environmental commitment and green human resource management (HRM) practices. This paper attempts to resolve the research problem by analysing the moderating effect of transformational leadership style on green HRM practices with employee environmental commitment and green service recovery performance in the hotel industry. The present study recruited 489 front-line employees and their 24 direct managers. The research results reveal that employee's environmental commitment mediates the relationship between green HRM practices and green service recovery performance. Moreover, the transformational leadership style moderates the relationship between green HRM practices and employee environmental commitment in the hotel industry. The study has critical insights and implications for hotel managers and theory.